Estudio ab-initio de la estabilidad de las propiedades estructurales y electrónicas del Bi1-xMgxO (2014)
Using the method in first-principles, we have investigated the structural and electronic properties of the compound Bi1-xMgxO with concentrations varying of 0%, 25%, 50%, 75% and 100% x of bismuth in the phase NaCl.We  have  used  the Full  Potential  Linearized  Augmented  Plane  Wave  Method  (FP-LAPW).  The  exchange and  correlation  effects  are  treated  using  the  Generalized Gradient Approximation (GGA) as it is implemented in the Perdew - Burke- Ernzerhof- method [1].